Comparative Study of Histopathologic Responses of Dog's Dental Pulp to Formocresol vs.15.5% Ferric Sulfate after Pulpotomy - E Jabbarifar; P Deyhimi; S Moradkhani (Isfahan University of Medical Sciences, 2006)
•Introduction: Pulpotomy is one of the most common treatments in Pediatric dentistry. Variousmodalities and materials have been applied in human and animal clinically. These procedures havebeen evaluated clinically, radiographically and rarely histopathologically. The purpose of this study iscomparison of histopathologic reaction of dog's dental pulp to formocresol (standard procedure) andferric sulfate (new modality).•Methods and Materials: Forty dog's sound permanent teeth were selected. After Anesthetizing ofanimal, 20 teeth was randomly pulpotomised, with formocrosol and 20 teeth with 15.5% ferric sulfate.After one month, animal was anesthetized again and sacrificed by vital perfusion. After that, teeth weredissected from Jaws and sent to Isfahan oral histopathology lab. Histologic sections were blindlyobserved by oral pathologist and reported state of inflammation, depth of inflammation, calcification,dentinal bridge, internal resorption and necrosis. Then frequency and relative frequency of theseparameters were analyzed by Chi-square and Mann-Whitney in SPSS software.•Results: Inflammation was not observed in 70% formocresol group and 75% ferric sulfate group.Calcification was not observed in 75% ferric sulfate group and 80% formocresol group. Necrosis wasnot observed in 55% ferric sulfate group and 65% formocresol group. Dentinal bridge was notobserved in 65% formocresol group and 45% ferric sulfate group.•Conclusion: Considering the findings of this study and other studies, insignificant differences betweenthe results in two groups, and also other aspects and characteristics, ferric sulfate can be one of properalternative pulpotomy modalities in primary dentition and developing permanent teeth.•Key words: Pulpotomy, Formocresol, Ferric sulfate, Histopathologic, Responses, Animal study.